2006
DOI: 10.5194/angeo-24-1227-2006
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of short-period gravity waves at high-latitudes during the MaCWAVE winter campaign

Abstract: Abstract. As part of the MaCWAVE (Mountain and Convective Waves Ascending Vertically) winter campaign an allsky monochromatic CCD imager has been used to investigate the properties of short-period mesospheric gravity waves at high northern latitudes. Sequential measurements of several nightglow emissions were made from Esrange, Sweden, during a limited period from 27-31 January 2003. Coincident wind measurements over the altitude range (∼80-100 km) using two meteor radar systems located at Esrange and Andenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
(84 reference statements)
3
29
0
Order By: Relevance
“…Considering the results of the simulations, the MAARSY multi-beam observations are suitable to detect GW with similar properties as observed by Nielsen et al (2006) and Pautet et al (2011). This demonstrates that it should be possible to resolve GW from the radial velocity images and to determine the GW properties.…”
Section: Simulation Of the Quasi-simultaneous Scansmentioning
confidence: 87%
See 1 more Smart Citation
“…Considering the results of the simulations, the MAARSY multi-beam observations are suitable to detect GW with similar properties as observed by Nielsen et al (2006) and Pautet et al (2011). This demonstrates that it should be possible to resolve GW from the radial velocity images and to determine the GW properties.…”
Section: Simulation Of the Quasi-simultaneous Scansmentioning
confidence: 87%
“…Nielsen et al (2006) analyzed short-period gravity waves over Northern Norway using OH, Na and O 2 emission as well as meteor radar wind measurements from Andøya and Esrange. The observed GW showed horizontal wavelengths between 10-42 km and phase speeds of 29-72 m s −1 .…”
Section: Simulation Of the Quasi-simultaneous Scansmentioning
confidence: 99%
“…As a GW propagates through this layer, it modulates the line-of-sight brightness and rotational temperature of the airglow emission, which appears as coherent wave structure in sensitive all-sky imaging systems (e.g. Swenson and Mende, 1994;Taylor et al, 1995;Smith et al, 2000;Ejiri et al, 2003;Medeiros et al, 2003;Nielsen et al, 2006). Most of the time the waves appear near linear; however on occasions well-defined concentric rings of GWs are detected over or near severe thunderstorms (Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Suzuki et al, 2007;Yue et al, 2008).…”
mentioning
confidence: 99%
“…A merged temperature field compiled from data from multiple instruments during the MaCWAVE winter campaign (see Figure 13) has provided a comprehensive view of the large-and small-scale motions throughout the atmosphere (Williams et al, 2006a). An analysis of the airglow data obtained from ESRANGE revealed a variety of motions ranging from GWs having largely verticall propagating character (in contrast to many previous observations) as well as evidence of significant relatively large-scale instability structures accompanying the strong tidal shears (Nielson et al, 2006), the measured phase structures of which are shown at two times in Figure 14. The analyses surveyed here are now in press in a special MaCWAVE issue of Ann.…”
Section: Dynamics Of the Winter Polar Atmospherementioning
confidence: 97%